A journey of neuroendocrine carcinoma of the brain from the primary to metastatic tumor - Chaudhari, Sachin; Patel, Sachinkumar; Pradhan, Dipendra; Partha, Ghosh; Tiwari , Mona (Indian Journal of Case Reports, 2022)
The neuroendocrine tumors most commonly originate in the lung, liver, and gastrointestinal tract. They can be graded into a three-tiered system depending on their proliferation index. These tumors frequently metastasize to the regional lymph nodes. Neuroendocrine tumors of the brain are very rare. Most of them are metastatic and a handful of cases are primary. Hereby, we present a case of brain neuroendocrine carcinoma, which was solitary with no evidence of the primary tumor in the body at the time of neurosurgery. However, treating physicians vigilantly kept him on regular follow-up and investigated further. The patient was diagnosed to have a lesion in the lung 3 months after surgery. Thus, it was considered primary neuroendocrine carcinoma of the brain; however, regular follow-up and further positron emission tomography scan showed a small mass in the lung and adrenal gland. Based on this, a final diagnosis of metastatic neuroendocrine carcinoma of the brain was made.